The Role of Islamic Education Teachers in Fostering Diversity Among Students at SD Negeri 101953 Pantai Cermin, Pantai Cermin District, Serdang Bedagai Regency - Sartika, Henny; Purba, Nurhaibah; Ramanda, Yusnita (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2024)
This research aims to explore the role of Islamic Religious Education (PAI) teachers in fostering student diversity at SD Negeri 101953 Pantai Cermin. The study falls under the category of qualitative field research, focusing on investigating and describing the conditions or phenomena occurring in the field without manipulating variables. In this context, a descriptive approach is used to highlight the importance of the role of PAI teachers in creating an inclusive environment that respects diversity. The research was conducted during the second semester of the 2023-2024 academic year in May 2024. This study employs a qualitative approach using observation and interview techniques. The research sample involved PAI teachers and students at SD Negeri No 101953 Pantai Cermin. The results indicate that the role of PAI teachers is crucial in guiding students to appreciate and understand diversity. PAI teachers act as facilitators in creating an environment that promotes tolerance and cooperation among students from various backgrounds. Through an inclusive approach, PAI teachers are able to shape the character of students to respect differences and uphold the values of diversity.